Building Students' Critical Thinking Abilities Through Project Based Learning Models on Energy Transformation Material - Apriliyanti, H.; Wardani, I. S.; Rusminati, S. H. (Universitas Negeri Yogyakarta, 2025)
The research examined the issue of low critical thinking skills of students in Natural and Social Sciences (IPAS), which is linked to their low engagement and involvement in learning activities. The study aimed to assess the effect of the Project-Based Learning model on improving students' critical thinking skills, particularly in the context of energy transformation topics. The research used a Quasi-Experimental Design, by following the Nonequivalent Posttest Only Control Group Design. The population were all students at SDN Dukuh Menanggal 1 Surabaya for the 2023/2024 school year. Sample selection technique used a purposive sampling, which selected 30 students from class IV-A and 30 students from class IV-B. The research showed that the post-test scores in the experimental class were higher, with an average score of 87.4. Meanwhile, the control class obtained a score of 71.9. Inferential analysis was conducted using SPSS 26 to test for normality, homogeneity, and hypotheses. The normality and homogeneity tests indicated that the distributions of both classes are normal and homogeneous. Based on the hypothesis test using the Independent Sample T-test, a significance level of 0.000 was obtained, which means that the Project-Based Learning model has a significant effect on developing students' critical thinking abilities in IPAS on the topic of energy transformation.